2012
DOI: 10.1007/s00262-012-1275-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining a peptide vaccine with oral ingestion of Lentinula edodes mycelia extract enhances anti-tumor activity in B16 melanoma-bearing mice

Abstract: New anticancer vaccines must overcome regulatory T cell (Treg)-mediated immunosuppression. We previously reported that oral ingestion of Lentinula edodes mycelia (L.E.M.) extract restores melanoma-reactive T cells in melanoma-bearing mice via a mitigation of Treg-mediated immunosuppression. In this study, we investigated the effect of oral ingestion of the extract on peptide vaccine-induced anti-tumor activity. The day after subcutaneous inoculation in the footpad with B16 melanoma, mice were freely fed the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Various mice studies also investigated the effects of β-glucan intake on subsets of immune cells within TME, blood or other organs. There were 7 out of 16 studies that reported increased IFN-γ production following ex-vivo stimulation of either blood-derived T cells, splenocytes, cells from tumor or immune tissues, following uptake of β-glucans [106][107][108][110][111][112][113]. In the study where cells from GALT showed increased IFN-γ production following ex-vivo stimulation, authors argued that administered WGP β-glucans induced IL-12 and TNF-α production by DCs and stimulated DC migration into the tumor, which resulted in local expansion of T cells [108].…”
Section: Supportive Effects Of β-Glucans Toward Adoptive T Cell Theramentioning
confidence: 99%
“…Various mice studies also investigated the effects of β-glucan intake on subsets of immune cells within TME, blood or other organs. There were 7 out of 16 studies that reported increased IFN-γ production following ex-vivo stimulation of either blood-derived T cells, splenocytes, cells from tumor or immune tissues, following uptake of β-glucans [106][107][108][110][111][112][113]. In the study where cells from GALT showed increased IFN-γ production following ex-vivo stimulation, authors argued that administered WGP β-glucans induced IL-12 and TNF-α production by DCs and stimulated DC migration into the tumor, which resulted in local expansion of T cells [108].…”
Section: Supportive Effects Of β-Glucans Toward Adoptive T Cell Theramentioning
confidence: 99%
“…Thus, we have created a vaccination platform technology that is able to break immune tolerance. Other vaccination technologies have been discovered that are also able to break immune tolerance, and it will be of interest to compare them with the technology employed in the current study (O et al, 2003;Yamano et al, 2006;Tanaka et al, 2012;Vasievich et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our vaccination technology can potentially be used in conjunction with immune-modulating agents to further enhance the vaccine potency. Previously, Tanaka et al (2012) demonstrates an immune-modulating agent, Lentinula edodes mycelia, mitigating immune suppression by Tregulatory cells can be used to improve TRP2 peptide-based vaccine potency. They demonstrate that TRP2 peptide-based vaccination in conjunction with immune-modulating agent Lentinula edodes mycelia can further enhance the antigenspecific immune response as well as the therapeutic antitumor effect against TRP2-expressing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, so far, several studies have used model antigens like ovalbumine‐expressing B16 melanoma cells , whereas relatively few endogenous tumour antigens have been characterized and tested in mouse models. Most studies with B16 cells have used gp100 or TRP2 as standard endogenous tumour antigens, whereas many recently defined tumour antigens are less immunogenic . Thus, characterization of new and potent MHC class‐I‐binding CD8 + T‐cell epitopes is essential for further preclinical cancer vaccine development.…”
Section: Introductionmentioning
confidence: 99%